The open empire a history of China to 1800 - Hansen, Valerie 1958- (W.W. Norton & Company, 2015)
The use of Pinyin -- Part I. Inventing China (ca. 1500 B.C.E.-200 C.E.) -- The beginnings of the written record -- The age of the warrior and the thinker : Double Ears and Confucius (770 B.C.E.-221 B.C.E.) -- The creation of empire (221 B.C.E.-200 C.E.) -- Part II. Facing west (C.E. 200-1000) -- China's religious landscape (200-600) -- China's golden age (589-755) -- The An Lushan Rebellion and its aftermath (755-960) -- Part III. Facing north (1000-1600) -- Coming to terms with money : the Song Dynasty (960-1276) -- The northern dynasties : non-Chinese rule in North China (907-1215) -- The Mongols (ca. 1200-1368) -- Continuing the war against the Mongols : the Ming Dynasty (1368-1644) -- The Qing empire (1636-1800) -- Epilogue
Includes bibliographical references and index
Keywords: Geschichte Anfänge-1800; China; China / History / To 221 B.C; China / History / 221 B.C.-960 A.D; China / History / 960-1644; China / History / 1644-1795